2018
DOI: 10.12659/msm.908133
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Protects Against Traumatic Brain Injury-Induced Acute Lung Injury in Mice

Abstract: BackgroundTraumatic brain injury (TBI) leads to acute lung injury (ALI), in which the inflammatory response plays an important role in its pathophysiology. Recent studies suggest that dexmedetomidine (Dex) plays a protective role in acute inflammatory diseases. However, whether Dex has a protective effect on TBI-induced ALI is not clear. The aim of this study was to investigate the effect of Dex on TBI-induced ALI in mice.Material/MethodsMice were randomly divided into 5 groups: 1) sham group; 2) TBI group; 3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
0
7
1
Order By: Relevance
“…provided us with notable insights into the neuroprotective effect of Dex [4,7,10,15,[29][30][31][32][33][34]. In this study, the expressions of IL-1b, TNF-a, IL-6, and IL-8 were significantly suppressed in the Dex group when compared to the I/R group, indicating that Dex plays a clear anti-inflammatory role in amelioration of cerebral I/R injury.…”
Section: Animal Studymentioning
confidence: 52%
“…provided us with notable insights into the neuroprotective effect of Dex [4,7,10,15,[29][30][31][32][33][34]. In this study, the expressions of IL-1b, TNF-a, IL-6, and IL-8 were significantly suppressed in the Dex group when compared to the I/R group, indicating that Dex plays a clear anti-inflammatory role in amelioration of cerebral I/R injury.…”
Section: Animal Studymentioning
confidence: 52%
“…A previous study revealed that DEX significantly reduces mortality and decreases the levels of inflammatory cytokines during endotoxemia in rats [39]. DEX reduces sepsis-related acute lung injury and has a protective effect on ischemia-reperfusion injury of the heart, brain, kidneys, and intestine in animal model [40][41][42][43]. DEX affects the immune cell ratio and suppresses inflammatory cytokine production in spleen and lymphocytes [44].…”
Section: Discussionmentioning
confidence: 98%
“…The mechanisms for the inhibition of autophagy may include the potent anti-inflammatory property of DEX. In a TBI-induced ALI mouse model, a single dose of 50 µg/kg DEX exerted protective effects via suppression of HMGB-1 signal transduction in the lung tissue [ 36 ]. A study in a rat model of sepsis-induced ALI revealed that treatment with 10–20 µg/kg DEX inhibited lung inflammation by suppressing the TLR4/MyD88/NFκB [ 37 ].…”
Section: Discussionmentioning
confidence: 99%